2014
DOI: 10.1007/s11282-014-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Signal intensity on fluid-attenuated inversion recovery images of condylar marrow changes correspond with slight pain in patients with temporomandibular joint disorders

Abstract: ObjectivesEdema and necrosis of the temporomandibular joint (TMJ) have been described in terms of bone marrow signal abnormalities in magnetic resonance imaging (MRI). However, painful joints often show no such signaling abnormalities, making the diagnosis of TMJ disorders difficult in the clinical setting. An association has been suggested between TMJ bone marrow change and TMJ pain, but even when such change results in slight pain, it may be too slight to be visually apparent on MR images. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
10
1
1
Order By: Relevance
“…Some studies have reported that FLAIR improved tissue contrast in the presence of degenerative disease of the cervical spine area and brain lesions [10][11][12] . It has also been reported that there is a potential use for FLAIR imaging in patients with vascular malformations and to assess condylar bone marrow changes in temporomandibular joint disorders 14,15) . The FLAIR sequence, however, has not come into common use in the oral and maxillofacial region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that FLAIR improved tissue contrast in the presence of degenerative disease of the cervical spine area and brain lesions [10][11][12] . It has also been reported that there is a potential use for FLAIR imaging in patients with vascular malformations and to assess condylar bone marrow changes in temporomandibular joint disorders 14,15) . The FLAIR sequence, however, has not come into common use in the oral and maxillofacial region.…”
Section: Discussionmentioning
confidence: 99%
“…FLAIR, an MRI sequence, has important roles in brain imaging [10][11][12] and has recently been used to examine pathological areas in the eye 13) . There are few reports, however, of the potential use of FLAIR in the oral and maxillofacial region 14,15) . In the present retrospective study, we qualitatively and quantitatively evaluated MRI sequences, including FLAIR, for their value in identifying multilocular ameloblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kodama et al [77] referred to the usefulness of fluid-attenuated inversion recovery (FLAIR)-sequence MRI to detect such minimal bone marrow changes. Signal intensity on FLAIR images is significantly higher in painful than in non-painful TMJs [77].…”
Section: Bone Marrow Abnormalities-related Joint Painmentioning
confidence: 99%
“…It has been stated that fat-suppressed T2-weighted MR imaging is useful for the detection of the marrow edema pattern in the mandibular condyle associated with TMJ-related pain [75] , [76] . Furthermore, Kodama et al [77] referred to the usefulness of fluid-attenuated inversion recovery (FLAIR)-sequence MRI to detect such minimal bone marrow changes. Signal intensity on FLAIR images is significantly higher in painful than in non-painful TMJs [77] .…”
Section: Bone Marrow Abnormalities-related Joint Painmentioning
confidence: 99%
See 1 more Smart Citation